Assessing eutrophication in transitional waters: A performance analysis of the Transitional Water Quality Index (TWQI) under seasonal fluctuations. (5th January 2019) - Bonometto, Andrea; Giordani, Gianmarco; Ponis, Emanuele; Facca, Chiara; Boscolo Brusà, Rossella; Sfriso, Adriano; Viaroli, Pierluigi
Abstract: The Transitional Water Quality Index (TWQI) is a simple tool for assessing the trophic status in shallow transitional water ecosystems, that can be easily implemented from basic monitoring activities. It integrates six metrics: the main causal factors of eutrophication (N and P concentrations), key biological elements (phytoplankton chlorophyll- a, benthic phanerogams and macroalgal cover) and an indicator of the eutrophication effects (dissolved oxygen saturation). This paper investigates the effectiveness of the TWQI to increase the confidence in trophic status assessment and to reduce the uncertainty due to temporal variability. The temporal variability of TWQI and its six single metrics, individually considered, were investigated in Venice Lagoon using data from 29 stations, sampled in July and October 2010, and 8 stations sampled monthly from April 2014 to March 2015. TWQI resulted less affected by seasonal fluctuations than the individual metrics, generally reducing the mean temporal variability by at least 50%. The influence of monitoring frequency on the uncertainty of the trophic status assessment was investigated as percent error of the TWQI annual mean. Means were firstly obtained from 12-monthly samplings. Lower sampling frequencies were also simulated and the deviation from the annual mean derived by monthly sampling was estimated. Overall, the annual mean values of TWQI was much less affected by the sampling frequency than individual indicators (e.g. Dissolved Inorganic Nitrogen). Based on the performance analysis of this study that demonstrates its reliability and efficiency, the TWQI can be recommended as a routine index to be used in large-scale monitoring of the trophic status in shallow transitional water ecosystems.